The complete chloroplast genome sequence of Hibiscus syriacus L. ‘Mamonde’ (Malvaceae) - Yongsung Kim; Yu Jin Oh; Kweon Young Han; Geun Ho Kim; Jaeyoung Ko; Jongsun Park (Mitochondrial DNA. Part B. Resources, 2019)
Hibiscus syriacus L. belonging to family Malvaceae is a hardy deciduous shrub and is distributed in warm-temperature region. To understand the genetic diversity of ‘Mamonde’ cultivar, of which flower colour is white and its center is red, complete chloroplast genome sequence of H. syriacus L. ‘Mamonde’ was sequenced. Its length is 161,025 bp and has four sub-regions: 89,179 bp of large single copy (LSC) and 19,816 bp of small single copy (SSC) regions are separated by 25,745 bp of inverted repeat (IR) regions including 131 genes (86 coding regions, 8 rRNAs, and 37 tRNAs). The overall GC contents of the chloroplast genome were 36.8% and in the LSC, SSC, and IR regions were 34.7%, 31.1%, and 42.8%, respectively. This chloroplast genome will be a useful resource for understanding cultivar specific genetic variations of H. syriacus.